Quantitative resilience assessment on critical infrastructures – A systematic literature review of the last decade (2014-2024) - Andrea De Marco; Davide Berardi; Marta Galuppi; Mara Lombardi (Journal of Safety Science and Resilience, 2025)
The everyday functioning of infrastructures and the capacity of their owners to provide high-quality services are critical to the well-being of communities and societies. When disruptions endanger society's well-being, security, and economy, some of these infrastructures are relevant and, as a result, are designated as critical for an entire nation. Therefore, research has focused on a peculiar infrastructure ability, or capacity, that summarizes these concepts in one word: resilience; its quantification, however, is not straightforward. Many authors have attempted to assess resilience using different subjects, infrastructures, resilience phases, and models. Therefore, through a systematic literature review based on the PRISMA protocol, this work presents an overview of quantitative methods and techniques developed over the past decade to numerically assess the resilience of critical infrastructures (CIs). A total of 111 papers were included in the study, which focused on studies published between April 2014 and April 2024. This article focuses on a model-based classification, highlighting strengths and weaknesses in the proposed methodologies, and performs a SWOT analysis on the modeling approaches identified within the retrieved papers. Future works could be useful to extend this research to those papers that describe and quantify single domains, stages, and features of CIs resilience, exploring the possibility of searching protocols to identify and correctly address them.